Information and Communication Technology Use by Agriscience Teachers in Trinidad and Tobago - Wayne Ganpat; Marcus Ramdwar; Christopher T Stripling; Grady T Roberts (Journal of International Agricultural and Extension Education, 2013)
The purpose of this study was to investigate information and communication technologies (ICT) usage among Agriscience teachers in Trinidad and Tobago. This knowledge will be used to develop preservice and inservice professional development programming for these teachers. Eighty-five percent (n = 77) of the secondary Agriscience teachers responded to a survey that assessed: (a) technology current use, (b) technology beliefs, (c) technology skills, (d) technology intentions, (e) barriers to technology use, and (f) personal data. Results indicated that Agriscience teachers in Trinidad have accepted ICT as useful tools. Teachers used ICT most frequently for personal reasons and less frequently for school-related tasks. Teachers generally believed that ICT help them accomplish tasks more quickly, enhance their quality of work, were easy to use, and that it could help to keep in touch with their students. However, beliefs varied based on age, career intentions, and computer literacy. Agriscience teachers also indicated that they possessed moderate skill levels and intend to use ICT as a part of their jobs. Differences in perceived skills were noted based on age, experience, and career intentions. Primary barriers centered on technical issues such as lack of hardware, inadequate technical infrastructure, and connectivity. Additionally, teachers believed that lack of a reward structure impeded technology usage.
Keywords: Agriscience Teachers; ICT; Information and Communication Technologies; Trinidad and Tobago